From Context to Studio Experience: A Paradigm Shift in Architectural Representation and Material Exploration - Selin Ozturk Demirkiran (Buildings, 2025)
This research explores a studio experience conducted at the Department of Architecture, Gebze Technical University, focusing on the integration of tectonic housing concepts into architectural design education. The study adopts a comprehensive methodology combining phenomenological readings, material experimentation, and contextual analysis through seminars, workshops, and studio projects. Innovative and experimental approaches were employed to move beyond traditional representation techniques, enabling students to engage with architecture through dynamic and multisensory methods. Findings demonstrate that this approach significantly enhances students’ creative capacities, fosters environmental responsiveness, and promotes a deeper understanding of the built environment. The study concludes that integrating tectonic interpretations into studio education can offer a transformative model for future architectural practice, providing a sustainable and human-centered design framework for architectural education and research.